2016
DOI: 10.1080/17474124.2017.1260002
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of benign esophageal strictures: a literature review

Abstract: Benign esophageal strictures arise from various etiologies and are frequently encountered. Although endoscopic dilation is still the first-line therapy, recurrent strictures do occur in approximately 10% of the cases and remains a challenge to gastroenterologists. Areas covered: A literature search was performed using PubMed and Google Scholar databases for original and review articles on endoscopic treatment of benign esophageal strictures. This review outlines the main available treatment options and its con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 109 publications
0
44
0
Order By: Relevance
“…In these series, all but 4 patients (from the Altintas’ study) who underwent steroid injection of the stricture had peptic injury (25 patients in total) (61, 62). The efficacy of steroid injection as adjunctive treatment remains unclear in other types of benign strictures (63). Apart from encouraging results reported in uncontrolled studies (59), well-designed studies showed mixed findings.…”
Section: Treatmentmentioning
confidence: 99%
“…In these series, all but 4 patients (from the Altintas’ study) who underwent steroid injection of the stricture had peptic injury (25 patients in total) (61, 62). The efficacy of steroid injection as adjunctive treatment remains unclear in other types of benign strictures (63). Apart from encouraging results reported in uncontrolled studies (59), well-designed studies showed mixed findings.…”
Section: Treatmentmentioning
confidence: 99%
“…Complex strictures, however, are difficult to treat being longer (> 2 cm), angulated or with severely stenosed lumen [2]. Approximately 20 % to 30 % of benign strictures can become refractory to endoscopic dilation, and as many as 50 % in cases of corrosive strictures [3]. Factors determining response to endo-therapy have been the point of much research.…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms can be atypical chest pain, heartburn and odynophagia. BRES significantly impair the quality of life and may cause severe complications, most importantly weight loss due to malnutrition, but aspiration and regurgitation may occur too[ 3 ]. Patients with BRES need regular endoscopic dilations and it is not uncommon that the stricture recurs in days or weeks, necessitating frequent repeat procedures, in some cases multiple times a month.…”
Section: Introductionmentioning
confidence: 99%